Il paesaggio storico delle Cinque Terre - Maristella, Storti (Scuole di dottorato, 2005)
The PhD thesis presented here investigates the historic landscape of the Cinque Terre through analysis of the multiform territorial iconography, descriptions of the past and the ancient cadastral records. The aim is to define a methodology (which could possibly also be extended to other contexts) for the qualitative appraisal of the landscape, where the yardstick is yielded by the abstract status conditions brought to light by parameters defined as "historic indicators". The temporal thresholds analysed (1612, 1643, 1799, 1918-32, 1982, 1990) lead to interpretative syntheses (for example, those on Riomaggiore) aimed at the identification of rules for project initiatives shared by the local communities.